Integrasi Pendidikan Seksual dengan Agenda Pembangunan Berkelanjutan: Strategi untuk Menangani Pernikahan Usia Muda - Delliana, Santi; Latabulo, Dholley Dwi Jatmiko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the relationship between sex education and the achievement of Sustainable Development Goals (SDGs) in Ciseeng Village, Bogor. Qualitative research methods, such as in-depth interviews with local stakeholders, field observations, and document analysis, were used to gain insight into the integration of sex education in educational settings. The research results show that almost all informants emphasized the importance of these three factors in understanding the phenomenon of early marriage in the region. In order to achieve the Sustainable Development Goals (SDGs) to reduce the growth rate of early marriage, several steps can be taken in Ciseeng Village, such as socializing the importance of mature marriage. The understanding that marriage is a process that requires physical and psychological readiness and the general understanding of marriage in Ciseeng Village is better understood as a natural part of human nature. The conclusion is that education, economics and culture are the main influences on the high rate of early marriage in Ciseeng Village. Keywords: Integration of Sexual Education, Young Marriage